1978
DOI: 10.1002/chin.197803379
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: CARBON‐13 NUCLEAR MAGNETIC RESONA

Abstract: Für das antibiotische Anthelmycin 148 wird die Struktur (I) bestätigt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…The reaction between the dialdose derivative (3) and (methoxycarbonylmethy1ene)triphenylphosphorane in methanol at ca. 4°C furnished the (a-olefin (8), which then gave (2)-6,7-dideoxy-1,2 : 3,4-di-O-isopropylidene-a-~-galacrooct-6-enopyranose (9) on reduction with lithium aluminium hydride. ' H N.m.r.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction between the dialdose derivative (3) and (methoxycarbonylmethy1ene)triphenylphosphorane in methanol at ca. 4°C furnished the (a-olefin (8), which then gave (2)-6,7-dideoxy-1,2 : 3,4-di-O-isopropylidene-a-~-galacrooct-6-enopyranose (9) on reduction with lithium aluminium hydride. ' H N.m.r.…”
Section: Resultsmentioning
confidence: 99%
“…In most instances, the stereochemical outcome of the osmylation reactions can be predicted by Kishi's empircal rule," the osmylation of the conjugate ester (8) providing a notable exception. The following paper describes further two-carbon extension of the chain of such octose sugars as (18) and (33) (2)-6,7-Dideoxy-1,2 : 3,4-di-0-isopropylidene-a-~-galacto-oct -6-enopyranose (9).-Lithium aluminium hydride (0.362 g, ca. 9.5 mmol) was added gradually to a cooled (0 "C) and stirred solution of the conjugate ester (8) …”
Section: Resultsmentioning
confidence: 99%
“…longissimus and Str. Hikiziensis [39]. Analysis of the degradation products revealed that anthelmycin contains cytosine, 3-amino-3-deoxy-D-glucopyranose (canosamine) and 4-aminoundecose (hikosamine).…”
Section: Natural Disaccharide Nucleosidesmentioning
confidence: 98%
“…Analysis of the degradation products revealed that anthelmycin contains cytosine, 3-amino-3-deoxy-D-glucopyranose (canosamine) and 4-aminoundecose (hikosamine). The -configurations of O-and N-glycosidic bonds of both amino sugars were established by NMR spectroscopy [39]. The antibiotic manifests antiparasitic and fungicidal properties and inhibits prokaryotic and eukaryotic peptidyl transferase [40].…”
Section: Natural Disaccharide Nucleosidesmentioning
confidence: 99%
“…hikiziensis. 28,29 Analysis of the degradation products of compound 22 revealed that the latter contains cytosine, 3-amino-3-deoxy-D-glucopyranose (canosamine) and 4-aminoundecose (hikosamine). 29,30 The b-configurations of Oand N-glycosidic bonds of both amino sugars were established by NMR spectroscopy.…”
Section: Structures and Properties Of Natural Disaccharide Nucleoside...mentioning
confidence: 99%